Pay System in Improving Job Satisfaction - Arlen Mardayanti; Hapzi Ali; Ahmad Syukri; Kasful Anwar Us; Afif Fuadi (Journal of Accounting and Finance Management, 2021)
This article discusses and analyzes the influence of the pay system, organizational culture and leadership style on job satisfaction, as an additional insight for teachers and prospective teachers so they can understand the things that affect job satisfaction. The method of writing this Literature Review article uses library research methods sourced from online media such as Google Scholar, Mendeley and/or other academic online media. The results of this article are: 1) the payroll system has an effect on job satisfaction; 2) organizational culture influences job satisfaction; and 3) leadership style influences job satisfaction. In addition to these 3 exogenous variables that affect endogenous variables in job satisfaction, there are many other factors including the work environment, working conditions, job security.